2017
DOI: 10.1111/jipb.12524
|View full text |Cite|
|
Sign up to set email alerts
|

ORA59 and EIN3 interaction couples jasmonate‐ethylene synergistic action to antagonistic salicylic acid regulation of PDF expression

Abstract: Hormonal crosstalk is central for tailoring plant responses to the nature of challenges encountered. The role of antagonism between the two major defense hormones, salicylic acid (SA) and jasmonic acid (JA), and modulation of this interplay by ethylene (ET) in favor of JA signaling pathway in plant stress responses is well recognized, but the underlying mechanism is not fully understood. Here, we show the opposing function of two transcription factors, ethylene insensitive3 (EIN3) and EIN3-Like1 (EIL1), in SA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…SA suppressed JA-responsive gene expression by downregulating ORA59 accumulation. In agreement with this, ORA59 overexpression in plants counteracted the SA-mediated antagonistic effect on JA-mediated PDF1.2 expression ( Leon-Reyes et al, 2010 ; Van der Does et al, 2013 ; He et al, 2017 ).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…SA suppressed JA-responsive gene expression by downregulating ORA59 accumulation. In agreement with this, ORA59 overexpression in plants counteracted the SA-mediated antagonistic effect on JA-mediated PDF1.2 expression ( Leon-Reyes et al, 2010 ; Van der Does et al, 2013 ; He et al, 2017 ).…”
Section: Introductionsupporting
confidence: 78%
“…To date, several transcription factors that interact with ORA59 and RAP2.3 have been reported. He et al (2017) demonstrated that ORA59 interacts with EIN3, and this interaction is required for SA-mediated reduction in ORA59 protein levels. RAP2.3 was associated with DELLA proteins ( Marín-de la Rosa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
“…EIN3 is the transcription factor with the largest role in ethylene signaling (128,139) and it homodimerizes to interact with its target DNA (141). However, environmental factors such as dark versus light or the presence of other hormones can affect this so that depending on conditions, EIN3 interacts with other transcription factors leading to outputs not predicted by the common ethylene signaling models (179)(180)(181). As an example, ethylene is well known for inhibiting hypocotyl growth in dark-grown eudicot seedlings (36,182) and stimulating hypocotyl growth in the light (183)(184)(185)(186)(187).…”
Section: Non-canonical Signalingmentioning
confidence: 99%
“…Jasmonic acid (JA), an important phytohormone that participates in many physiological processes and stress responses in plants (Robert‐Seilaniantz et al ; He et al ; Hickman et al ; Sarde et al ; Howe et al ), is also known to be involved in the response to Cd stress, with JA promotion of Cd tolerance being reported. For example, Cd induced the expression of JA synthesis and JA‐response genes (Cabot et al ; Keunen et al ), and a biphasic‐modal accumulation of JA was observed in the mature leaves of Arabidopsis (Maksymiec et al ).…”
Section: Introductionmentioning
confidence: 99%